ZIRCONIUM POLYMER CHARACTERISTIC AS 99Mo / 99mTc GENERATOR ABSORBENT FOR DIAGNOSTIC RADIOPHARMACEUTICALS - Umi Nur Sholikhah; Hotman Lubis; Endang Sarmini; Herlina Herlina; Kadarisman Wisnukaton (Widyariset, 2016)
One of the radiopharmaceuticals that were used for diagnostic is conducted by using Technetium-99m (99mTc), which could be obtained from Molybdenum-99 (99Mo) separation. This research was conducted to determine the adsorbent polymer variation effect at two zirconium chromatography systems to obtain 99mTc yield more than 80%. Polymers were used zirconium-TEOS as adsorbents in the first system while the second system used Zirconium-TEOS-methanol. The same method was conducted for both systems. The preparation was done by adding 99Mo on both polymers and heated at 90 °C temperature for three hours. Elution process of 99Mo and 99mTc was conducted by using column chromatographic system, in which the column filled with Alumina is connected to the Zirconium polymer column. The elution process was conducted on the next day until 10th fractions. Both of the systems showed the 99mTc radionuclides were highest eluted at the 3rd fraction then they decline to constant at the 10th fraction. The 99mTc yield in the system 1 was 58% and the system 2 was 96.23%. The elution from the system 1 was not analyzed by Atomic Absorption Spectrometer (AAS) because the 99mTc yield was less than 80%. Analysis results using AAS on the system 2 found out that the system 2 contained Si 1.11 ppm, and no other elements (Mo and Zr) was obtained. Based on Lethal Dose 50 (LD50), it is showed that the elution of system 2 is below the threshold (Mo = 4000 mg /kg, Zr = 489 mg /kg and Si = 22.5mg /kg), therefore it was safe to be used for diagnostic radiopharmaceuticals.